DRESS syndrome due to vemurafenib treatment: switching BRAF inhibitor to solve a big problem. (30th September 2018) - Ros, Javier; Muñoz-Couselo, Eva
Abstract : We present a case report of an early-onset drug reaction with eosinophilia and systemic symptoms (DRESS syndrome) induced by vemurafenib (BRAF inhibitor) in a middle-age man affected by a metastatic, BRAF mutant melanoma who was started on first-line metastatic treatment with vemurafenib and cobimetinib. After initiating the treatment, the patient presented an extensive cutaneous rash with eosinophilia and renal impairment. Due the constellation of signs and symptoms, a diagnosis of DRESS syndrome was made which strongly contraindicated the reintroduction of vemurafenib due to its hypersensibility reaction. Thus, vemurafenib was stopped immediately, and we started corticoid treatment with clinical improvement. Due to the contraindication to start vemurafenib again, after multidisciplinary view of the case and having balanced the risks and benefits, we successfully performed a switch to another BRAF inhibitor in a progressively ascending pattern, without any skin toxicity and with a good response of the metastatic melanoma.